Analisis Prestasi dari Sudut Pandang Manajemen pada PT. Wijaya Karya Bangunan Gedung Tbk - Maharani, Yesy; Sari, Despita; Zakiah, Hafizahtul (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2025)
During the pandemic, almost all companies have difficulty in earning revenue and making profits, including PT Wijaya Karya Bangunan Gedung Tbk. The purpose of this study is to assess the financial performance of PT Wijaya Karya Bangunan Gedung Tbk using published financial report data from 2019 to 2022. The financial reports were accessed from the company's official website at https://www.wikagedung.co.id/. The data was then reviewed using a financial ratio formula based on management's perspective. The analysis shows that the pandemic has been a major burden on the company, especially in 2020 when PT Wijaya Karya suffered significant losses. However, when the pandemic began to end, the company's condition began to improve. However, the company still needs to continue to improve operational efficiency, control costs, and manage assets and receivables better so that the company's finances can be stable and sustainable in the future.